Damage analysis and optimal design of micro-structure milling cutter based on peridynamics. - Zhongwei Ren; Jing Deng; Hongwan Jiang; Sen Yuan; Xi Yue; Chuchun Tian (PLoS ONE)
H13 die steel has the characteristics of high hardness, strong toughness, and good heat resistance, and is a typical difficult to process materials material. During the cutting process, it is prone to accelerate tool wear and cause thermal deformation. By reasonably designing micro-grooves, the comprehensive performance of the tool can be effectively improved. In this study, by optimizing the structural parameters of the micro-groove, the comprehensive performance of the tool is significantly improved, and the micro-groove optimization control mechanism is deeply analyzed. At the same time, the micro-damage problem is numerically analyzed by using the peridynamics numerical simulation and comparison experiment. Research results indicate that properly increasing the distance between the slot at the outer contour of the cutting tool and the cutting edge and projecting it in a flattened shape onto the surface of the tool, ensures a smooth transition between the groove top and bottom near the cutting edge can effectively enhance the comprehensive performance of the cutting tool. The tool's major cutting edge near-field and rake face is prone to micro-cracks resulting in crack diffusion. When the milling time is 3.5×10-6 s, the tool's major cutting edge combined displacement increases most rapidly, the major flank optimization effect is the most obvious, and the resultant displacement is reduced by about 37.06%. By optimizing the structural parameters of micro-grooves on the rake face, this study enhances the comprehensive performance of the tool and unveils the formation, distribution, and variation patterns of near-field cracks on the tool's cutting edge. The research results have certain valuable insights for the optimization design and manufacturing of high performance milling tools made from H13 die steel.